Understanding the key phases of the countermovement jump force-time curve - McMahon, J.; Suchomel, T. J.; Lake, J. P.; Comfort, P. (Strength and Conditioning Journal, 2018)
The countermovement jump (cmj) test is commonly conducted to assess neuromuscular function and is being increasingly performed using force platforms. Comprehensive insight into athletes' neuromuscular function can be gained through detailed analyses of force-time curves throughout specific phases of the cmj, beyond jump height alone. Confusingly, however, many different terms and methods have been used to describe the different phases of the cmj. This article describes how 6 key phases of the cmj (weighing, unweighting, braking, propulsion, flight, and landing) can be derived from force-time records to facilitate researchers' and practitioners' understanding and application to their own practice.